Implementasi Pelayanan Prima di Restoran Internasional : Studi Kasus Mahasiswa Magang di Lanta Nice Beach Resort - Alif Bagus Prayoga; Rd Hera Merdeka K. K; Asfitri Hayati (Gemawisata: Jurnal Ilmiah Pariwisata, 2025)
This study aims to examine the implementation of excellent service by internship students at the restaurant of Lanta Nice Beach Resort, an international resort known for its high service standards. Excellent service is a key element in the tourism and hospitality industry, particularly in resort restaurants that cater to guests from diverse cultural backgrounds. This research adopts a case study method with a qualitative approach. Data were collected through observation, interviews with internship students and restaurant staff, and field documentation. The findings indicate that the internship students are able to apply excellent service principles, such as maintaining buffet cleanliness, timely food service, and using effective and friendly communication in English. Nonetheless, they face challenges in adapting to international work culture and using a foreign language in dynamic settings. This study recommends enhanced communication and stress management training for internship students to improve service quality. The findings are expected to serve as input for resort management in mentoring interns and for educational institutions in designing more contextual and effective internship programs aligned with the needs of the global hospitality industry.